Pilot survey on the conservation of historical buildings in Malaysia - Kamal, Kamarul Syahril; Ab Wahab, Lilawati; Ahmad, A. Ghafar (2008)
Historic buildings basically represents the single most visible aspect of our past history and culture. Like most other countries in the world, Malaysia has a rich legacy of historic buildings with outstanding craftsmanship and architecture quality. They form an impressive historic features and heritage of the past work of man. It is important to conserve and preserve historic buildings because they provide a sense of identity and continuity in a fast changing world for future generations. However some of these buildings are at risk from defects and are not being well cared for due to lack of technical knowledge and high cost of repair and maintenance. The purpose of this paper intends to highlight the existing conditions of historical buildings in Malaysia with the main focus on the conditions of building defects and conservation approach to these buildings. To do so, a pilot survey has been conducted on several heritage towns and cities based on the existing heritage trail in Malaysia. The broad objective of this pilot survey is to examine the level of building defects and the location of building defects that normally occur at various types of historical buildings in Malaysia. At the same time, it will also look into the conservation approaches that has been done to these historical buildings either the method are acceptable according to the basic principles and philosophy of building conservation. It is expected that this paper could contribute some benefits to the owners, consultants, contractors, conservators, various government agencies, heritage body and by all those who concerned with the care and conservation of historic buildings in Malaysia.